Effect of stretching program on low back pain and neck pain - Vidit Atul Phanse (North American Journal of Engineering Research, 2022)
Pain is the most symptomatic cause of the patient reporting to the medical profession. Every person has reported one in their lifetime about pain symptoms at medical consultancy. Neck and lower back are the commonest musculoskeletal related pain in all young adults. Stretching is the most used physical therapy among many in combination in the management of neck and back pain. However there in no clear studies that only discuss on effect of stretching program on neck and back pain. There for these is a short review on the aim to discuss the effectiveness of stretching program in neck and back pain. 5 highly relatable studies were selected for discussion in the present study. The study discussed the mechanism of active and passive stretching on pain. Study concluded that stretching is effective in treatment of neck and lower back pain as first line of treatment when the Couse id purely musculoskeletal. Thought desired changes can only be seen in long term bases and type of stretching programs